Schools and Society in the Perspective of the Qur'an - Amiruddin Siahaan; Mutiara Ritonga; Zuhud Suriono (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
His study aims to obtain an overview of the knowledge mapping of teachers at SDN 055979 Sei Tembo, Kuala District, Langkat Regency from the aspect of knowledge about the characteristics of K13, the principles of developing K13, the structure of K13 in Elementary Schools, Implementation of K13 and the Principles of developing lesson plans. This type of research is descriptive research. Data collection techniques used in this study were interviews and questionnaires. This research was conducted at SDN 055979 Sei Tembo, Kuala District, Langkat Regency. The subjects of this study were teachers of grades I, II, III, IV, V and VI who had implemented the 2013 curriculum. The population in this study was SDN 055979 Sei Tembo, Kuala District, Langkat Regency. The sample in this study were 6 teachers at SDN 055979 Sei Tembo, Kuala District, Langkat Regency. The results of this study indicate that the knowledge of teachers at SDN 055979 Sei Tembo is quite good. This can be seen from the answers given by the teacher on the questionnaire sheet. It's just that there are some teachers who do not know about K13 knowledge well, due to the lack of training and mentoring at SDN 055979 Sei Tembo, Kuala District, Langkat Regency. Thus it can be concluded that the teacher's knowledge of the 2013 curriculum is quite good.